The educational connections of critical thinking - Coin, Francesca (Formazione & insegnamento, 2017)
“Critical Thinking” appeared in Western culture in ancient times and has never been neglected. Its unquestioned importance was established in various fields and it is recognized as essential to a complete education plan. Its central position comes from some particular aspects. First, it was the trigger for one of the great revolutions of modern pedagogy: Dewey’s pedagogical activism movement, which shifted attention from the teachers and from the information, to the students and to their experiences’ processing. Secondly, critical thinking, by its own definition, covers many aspects of a person’s life: it is knowledge, it is appliance, but above all, it is an attitude; it influences people’s independence and so it has a great impact on whole society. It creates connections with all other forms of thought and acts as a transversal skill, which allows the continuous and fluid passage from a thinking form to another. To develop comprehensive and balanced individuals is appropriate to increase the education of critical thinking also in the contexts of formal education, so that training can start early and avoid some of the typical distortions of interpretation, to which we are naturally led. Educating critical thinking does not mean “make you think critically,” but only help you develop some basic skills of critical thinking. To do that, there is no universally strategy, but it only matter the variety of experiences that you can offer and the dialogue, the collaboration, which you create during this process.